2009
DOI: 10.1016/j.marenvres.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and trophic transfer of mercury in striped bass (Morone saxatilis) and tautog (Tautoga onitis) from the Narragansett Bay (Rhode Island, USA)

Abstract: We examined the bioaccumulation and trophic transfer of mercury in two marine finfish species, striped bass (Morone saxatilis) and tautog (Tautoga onitis), collected from the Narragansett Bay (Rhode Island, USA). For each of these target fish, white muscle tissue was analyzed for total mercury (Hg) and results were evaluated relative to fish age, body size, and Hg content of preferred prey. Dietary and stable isotope analysis was also used to elucidate the effect of trophic processes on Hg concentrations in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 51 publications
(72 reference statements)
4
57
0
1
Order By: Relevance
“…Mercury levels in Chinese freshwater fish are lower than those reported for fish in Canada (0.047-1.82 mg kg À1 ) [89], the United States (0.02-0.92 mg kg À1 ) [90,91], and Brazil (0.23-2.70 mg kg À1 ) [92]. Various studies have confirmed that the Hg concentration in fish is decided mainly by trophic level and age [93][94][95][96][97] and is less strongly correlated to the environmental Hg concentration. This finding has also been confirmed by a study in Tibet in which Hg concentrations in fish were found to be much higher than those in most fish samples from areas with high environmental Hg concentrations [98].…”
mentioning
confidence: 99%
“…Mercury levels in Chinese freshwater fish are lower than those reported for fish in Canada (0.047-1.82 mg kg À1 ) [89], the United States (0.02-0.92 mg kg À1 ) [90,91], and Brazil (0.23-2.70 mg kg À1 ) [92]. Various studies have confirmed that the Hg concentration in fish is decided mainly by trophic level and age [93][94][95][96][97] and is less strongly correlated to the environmental Hg concentration. This finding has also been confirmed by a study in Tibet in which Hg concentrations in fish were found to be much higher than those in most fish samples from areas with high environmental Hg concentrations [98].…”
mentioning
confidence: 99%
“…4). Comparable Hg-length (or weight) trends have been reported for bluefish in the Long Island Sound and coastal New Jersey [18,19,54], as well as other estuarine and coastal fishes from the northwestern Atlantic [6,7,54,56]. The significant positive correlation between bluefish muscle Hg and length affirms that Hg biomagnifies in this tissue, and is likely attributable to the rapid uptake of the contaminant relative to its excretion from the body [21,57].…”
Section: Mercury Contamination In Bluefish and Preymentioning
confidence: 73%
“…Isotope measurements of a subsample ($1 mg dry wt) of age 0 bluefish (muscle filet; n ¼ 20), age 1 þ bluefish (D 0 biopsy; n ¼ 20), and prey (whole body; n ¼ 20-85) were performed by the Boston University Stable Isotope Laboratory (Boston, MA, USA) [7]. Briefly, automated continuous-flow isotope ratio mass spectrometry was used to quantify isotopic signatures, and ratios of 15 C. The precision of the continuous-flow isotope ratio mass spectrometry method, as determined by the analysis of internal reference material (peptone and glycine), was 0.2% and 0.4% for nitrogen and carbon, respectively.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 2 more Smart Citations